The Restoration of New Gourna: Safeguarding the Legacy of Hassan Fathy - Heidi Shalaby; Haby Hosney Mostafa Ahmed (Journal of Traditional Building, Architecture and Urbanism)
Hassan Fathy’s New Gourna project in Egypt (1946-52) is renowned as a pioneering example of sustainable urban settlement, integrating traditional technologies with modern architectural principles and serving as an inspiration to architects and planners worldwide. But decades of neglect have resulted in major structural deterioration and demolitions of the original buildings. In response, a project titled “Safeguarding Hassan Fathy’s Architectural Legacy in New Gourna” has been undertaken through a collaboration between UNESCO and the Egyptian Ministry of Culture, as defined by the National Organization for Urban Harmony (NOUH) for the period 2019-21. This initiative aims to conserve and repurpose the public heritage buildings while addressing the critical issue of groundwater. NOUH has now taken the project into a second phase (2023-24). This paper outlines the symptoms and causes of deterioration in New Gourna Village and reviews the restoration efforts applied to four major buildings: the khan, the mosque, the theater, and Hassan Fathy’s house. Further research will detail the restoration project in each case, including the documentation phase and the specific restoration techniques applied to each structural element and material.